Efficacy of a repeat testing protocol for cognitive fatigue assessment: a preliminary study in postconcussive syndrome participants - Thomas F Rau; Sarjubhai A Patel; Erik E Guzik; Edmond Sorich; Alan J Pearce (Concussion)
Aim: A small but notable number of individuals who suffer a concussion report ongoing cognitive difficulties. This preliminary study investigated the efficacy of repetitive test application to discern cognitive impairment in those with ongoing symptoms. Methods: Participants (n = 17) with continuing self-reported symptoms following a concussion (∼9 months postinjury) were compared with 17 age group matched controls for working memory and word-list learning. Results: Both groups performed similarly after the first trial for both assessments. However, in subsequent trials, the postconcussion group performed significantly worse than controls. Discussion: While further studies to understand the mechanisms are warranted, data from this preliminary study suggest that a repetitive test application may be useful to discern cognitive fatigue in individuals who report ongoing concerns following a concussion.